Recurrent tracheoesophageal fistula in an adolescent without persistent symptoms: A case report. Issue 46 (November 2017) - Lin, Jun-Hong; Deng, Li; Li, Xing
Abstract: Rationale: Congenital esophageal atresia (EA) and tracheoesophageal fistula (TEF) ininfants have been treated well with surgery. Approximately 10% of children displayed recurrent fistula. In the present case, we reported recurrent TEF in an adolescent as a complication of EA/TEF in infancy. Patient concerns: An infant was diagnosed with gross type C congenital EA and TEF and subsequentlyunderwent repair in early infancy, with division of the TEF and primary esophageal anastomosis. Postoperative esophageal strictures developed and were relieved by bougienage of the esophagus partially. Then, the child had normal growth with mild symptoms, mainly choking when drinking water. At 11 years of age, the child developed fever and cough, and massive bronchiectasis in lobus inferior pulmonis sinister was found. Diagnosis: Recurrent tracheoesophageal fistula. Interventions: Division of the TEF and esophageal replacement with gastric tube was performed as treatment Outcomes: The child recovered well. Lessons: Recurrent tracheoesophageal fistula aftercongenital EA and TEF could be diagnosed in adolescence. Massive bronchiectasis might develop without apparent symptoms.